PENGARUH PENDAPATAN TERHADAP LOYALITAS DAN KEPUASAN KONSUMEN DENGAN KUALITAS PRODUK SEBAGAI VARIABEL MEDIASI PADA PEMAKAI KOSMETIK MUSTIKA RATU DI MADIUN - -, Retno Hendrajani (Universitas Slamet Riyadi, 2015)
The study aims to analyze the significance of the effect of income variable on consumer loyalty and consumer satisfaction, the variable quality of the product to customer loyalty and customer satisfaction, the variable income to product quality, the variable income on consumer loyalty and consumer satisfaction mediated quality of the products. The population in this study are end-users of cosmetic products Mustika Ratu are limited. The amount numbering no role in the study sample as many as 100 people. The sampling technique using quota sampling method. The technique of collecting data using questionnaires through validity and reliability. Techniques using multiple linear regression analysis with the classical assumption. The results obtained by analysis of the questionnaire of all variables is valid and reliable. so that it can be concluded that the variable positive and significant impact on customer satisfaction is the quality of products and customer loyalty; for variable negative and significant revenue to customer satisfaction. Test results coefficient of determination of income and product quality to customer loyalty 79,7%; Test results coefficient of determination of income and product quality to customer satisfaction for the remaining 24,2% influenced other variables. Conclusion of the study The hypothesis stating “Revenue significant effect on customer loyalty and consumer satisfaction, significantly influence consumer satisfaction, Quality of products have a significant effect on consumer satisfaction